1977
DOI: 10.1161/01.cir.56.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Re-entrant ventricular arrhythmias in the late myocardial infarction period. 4. Mechanism of action of lidocaine.

Abstract: SUMMARY The effect of lidocaine on re-entrant ventricular arrhythmias (RVA) was studied in dogs 3-7 days following ligation of the anterior descending coronary artery; direct recordings were made of the re-entrant pathway (RP) from the epicardial surface of the infarction zone (IZ). Lidocaine in a therapeutic dose consistently prolonged refractoriness of potentially RP(s) in the IZ and produced a higher degree of conduction block at a constant heart rate. Conduction in the adjacent normal zone was not affected. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Furthermore this effect is independent of rate. As partial depolarization is a well-known feature of myocardial ischaemia (see Janse & Kleber, 1981, for review), such a selective effect, already demonstrated for lignocaine (Kupersmith, Antman & Hoffman, 1975;El-Sherif, Scherlag & Lazzara, 1977), could well be of considerable clinical relevance. Finally, it should be noted that any effect on refractoriness due to this shift in the V,,-membrane potential relationship would only be minor, since membrane voltage is changing very rapidly with time during the terminal phase of the action potential.…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore this effect is independent of rate. As partial depolarization is a well-known feature of myocardial ischaemia (see Janse & Kleber, 1981, for review), such a selective effect, already demonstrated for lignocaine (Kupersmith, Antman & Hoffman, 1975;El-Sherif, Scherlag & Lazzara, 1977), could well be of considerable clinical relevance. Finally, it should be noted that any effect on refractoriness due to this shift in the V,,-membrane potential relationship would only be minor, since membrane voltage is changing very rapidly with time during the terminal phase of the action potential.…”
Section: Resultsmentioning
confidence: 86%
“…However, subsequently several different groups of investigators have studied the effects of acute ischemia on local electrophysiology with the use of bipolar electrodes (11)(12)(13)(14)(15)(16)(17)33). (36).…”
Section: Early Phase Arrhythmiasmentioning
confidence: 99%
“…Carsson has proposed that the failure in the propagation can favour a unidirectional block of wave front of the stimuli [4,5].…”
Section: Introductionmentioning
confidence: 99%